Environmental influences on microbial communities of lake whitefish, cisco, and Arctic char on and surrounding King William Island, Nunavut - Hamilton, Erin (2020)
Partnered with the Nunavut community of Gjoa Haven on King William Island, a large-scale Genome Canada project, the Towards a Sustainable Fishery for Nunavummiut (TSFN) project endeavoured to integrate Inuit traditional knowledge and practices with genomic and microbial analyses to assess the sustainability and health of the Coregonus species complex (CSC) and Arctic char (Salvelinus alpinus) fisheries. Encompassed within the goals of the project, fish health was assessed based on microbial diversity and condition factor (K) of the sampled fish. In this region, sampled CSC, which included lake whitefish (C. clupeaformis) as well as two cisco species (C. autumnalis and C. sardinella) and Arctic char displayed anadromy, transitioning annually from the ocean to freshwater lakes and rivers. Inuit fishers collected samples from the ocean, rivers, and lakes in different seasons, and microbiomes from these salmonids were characterized with respect to changing seasonal habitats. Skin- and intestine-associated microbiomes were characterized through amplification of 16S rRNA gene fragments. Overall, lake whitefish, ciscoes, and Arctic char skin-associated microbiota grouped separately in ordination based on salinity while cisco and Arctic char grouped based on seasonal habitat. Higher Shannon diversity in autumn and spring freshwater habitats suggested a transitional state in the autumn riverine and spring lacustrine environments. Core microbiomes, representing taxa found in at least 50% of samples, were also identified within seasonal habitats. Comparison of skin- and intestine-associated core microbiota showed differences in composition across seasonal habitats. Condition factor (K) remained consistent across seasonal habitats for cisco, was higher for lake whitefish in the lacustrine environment, and progressively decreased for char from ocean, to riverine, to overwintering habitat. There was some evidence of dysbiosis in the microbiota of lake whitefish, which may be associated with stress as these fish are at the ...